Antiglycation, antioxidant and cytotoxicity activities of crude extract of Turnera ulmifolia L. before and after microencapsulation process - Viel, Amanda Martins [UNESP]; Figueiredo, Célia Cristina Malaguti [UNESP]; Granero, Filipe Oliveira [UNESP]; Silva, Luciana Pereira; Ximenes, Valdecir Farias [UNESP]; Godoy, Thais Miranda; Quintas, Luis Eduardo Menezes; Silva, Regildo Márcio Gonçalves da [UNESP] (Elsevier, 2022)
Turnera ulmifolia L. is used in folk medicine and it is known to have anti-hyperglycemic effect on the organism in order to reduce complications in diabetic patients. Glycation process is directly related to oxidative stress, acting as an important endogenous source, inducing the production of free radicals, and thus increasing the production of reactive oxygen species. The encapsulation technology on natural compounds can minimize and even mitigate the risk of loss of biological activity in order to maintain their activities against oxidative stress and glycation. The present study aimed to evaluate the antiglycation and antioxidant activities of T. ulmifolia extract before and after encapsulation and cytotoxicity of the crude extract. This study presents important information about the biological activities, highlighting antioxidant and antiglycation potential and no cytotoxicity of Turnera ulmifolia crude extract, a species of genus Turnera that has been poorly studied. T. ulmifolia crude extract presented flavonoids as main active compounds. The results showed a promising activity in scavenging free and peroxyl radicals, chelating iron ions and inhibiting BSA glycation. In addition, this study showed the possible encapsulation of bioactive compounds using maltodextrin as wall material.
Keywords: Flavonoids; Microcapsules; Oxidative stress; Protein glycation; Turnera ulmifolia L